Analysis of Metacognition Ability and Critical Thinking Skills of Students in Integrated Islamic Education Institutions - sukarno -; AA Musyafa (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2021)
Abstract: Metacognition and critical thinking skills are essential elements in creating good quality and competitive humans in the future. Therefore, this study aims to describe students' metacognitive abilities and critical thinking skills in Integrated Islamic Junior High School in Jambi. The writer uses a quantitative approach in this study and survey techniques to collect the data. There are 200 students from various Integrated Islamic Junior High Schools in Jambi involved in this study. After validating the data through validated instruments, the research reveals that: (1) The highest metacognitive ability of students at the Integrated Islamic Junior High School is in Procedural Knowledge (PK), which is an average value of 7.4 in the